2018
DOI: 10.1039/c8nr01322e
|View full text |Cite
|
Sign up to set email alerts
|

An acid-compatible co-polymer for the solubilization of membranes and proteins into lipid bilayer-containing nanoparticles

Abstract: Positively charged poly(styrene-co-maleimide) extracts functional membrane proteins into nanodiscs, overcoming some limitations of current nanodisc technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 58 publications
2
118
0
Order By: Relevance
“…Despite the great potential, polymer nanodisks have suffered from some major drawbacks due to the intrinsic chemical properties of SMA inherent to its hydrophobic and hydrophilic units . Several studies have already shown an enhancement of SMA's stability by the modification of hydrophilic functional units . The most common hydrophobic group used in SMA polymer nanodisks is the styrene moiety.…”
Section: Properties Of Alkyl‐paa‐dmpc‐nanodisksmentioning
confidence: 99%
“…Despite the great potential, polymer nanodisks have suffered from some major drawbacks due to the intrinsic chemical properties of SMA inherent to its hydrophobic and hydrophilic units . Several studies have already shown an enhancement of SMA's stability by the modification of hydrophilic functional units . The most common hydrophobic group used in SMA polymer nanodisks is the styrene moiety.…”
Section: Properties Of Alkyl‐paa‐dmpc‐nanodisksmentioning
confidence: 99%
“…Polymers such as styrene maleimide copolymer-lipid nanoparticles (SMILPs) and styrene-maleic acid copolymer-lipid nanoparticles (SMALPs) can solubilize the protein of interest without the use of detergent. SMALPs and SMILPs form nearly homogenous nanoparticles and provide a native mimicking environment with lipids that are compatible with the protein of interest, while stabilizing the protein with minimal interference 15,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have used polymers to form membrane mimetic systems 14,15,28 and commercial polymers have been used to characterize the formation of lipodisq nanoparticles using dynamic light scattering (DLS), 31 P Solid State Nuclear Magnetic Resonance (SSNMR), and Transmission Electron Microscopy (TEM) 29 . Recently, our lab has shown that 3:1 styrene-maleic acid can be synthesized in a laboratory setting using reversible addition-fragmentation chain transfer polymerization (RAFT) polymerization and successfully used to characterize the structure of styrene-maleic acid copolymerlipid nanoparticles (SMALPs) 15,30 .…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of amphiphilic polymers that form lipid nanodiscs has most notably contributed to the study of membrane proteins (MPs) and allows for their functional and structural study in a tunable native‐like membrane environment . While polymer nanodiscs are the youngest of the nanodisc field, they are showing great potential due to the simplicity of their synthesis, their diverse chemical tunability, and their ability to directly extract membrane proteins from their cellular environment at practical cost . Nanodiscs are a useful tool for NMR spectroscopy since their size can be tuned to conditions favorable to both solution and solid‐state NMR.…”
Section: Figurementioning
confidence: 99%